A review on architecture of the gag-pol ribosomal frameshifting RNA in human immunodeficiency virus: a variability survey of virus genotypes. Issue 8 (11th June 2017) - Qiao, Qi; Yan, Yanhua; Guo, Jinmei; Du, Shuqiang; Zhang, Jiangtao; Jia, Ruyue; Ren, Haimin; Qiao, Yuanbiao; Li, Qingshan
Abstract : Programmed '-1' ribosomal frameshifting is necessary for expressing the pol gene overlapped from a gag of human immunodeficiency virus. A viral RNA structure that requires base pairing across the overlapping sequence region suggests a mechanism of regulating ribosome and helicase traffic during expression. To get precise roles of an element around the frameshift site, a review on architecture of the frameshifting RNA is performed in combination of reported information with augments of a representative set of 19 viral samples. In spite of a different length for the viral RNAs, a canonical comparison on the element sequence allocation is performed for viewing variability associations between virus genotypes. Additionally, recent and historical insights recognized in frameshifting regulation are looked back as for indel and single nucleotide polymorphism of RNA. As specially noted, structural changes at a frameshift site, the spacer sequence, and a three-helix junction element, as well as two Watson–Crick base pairs near a bulge and a C–G pair close a loop, are the most vital strategies for the virus frameshifting regulations. All of structural changes, which are dependent upon specific sequence variations, facilitate an elucidation about the RNA element conformation-dependent mechanism for frameshifting. These facts on disrupting base pair interactions also allow solving the problem of competition between ribosome and helicase on a same RNA template, common to single-stranded RNA viruses. In a broad perspective, each new insight of frameshifting regulation in the competition systems introduced by the RNA element construct changes will offer a compelling target for antiviral therapy.